Crenitis bicolor sp. n. from the Kamiesberg of South Africa (Coleoptera: Hydrophilidae) - Bilton, David T. (Zootaxa, 2013)
Crenits Bedel is a small hydrophilid genus of 41 species (Hansen, 1999; Hebauer, 1994, 2005), distributed acrossEurasia,Africa and theAmericas. The genus is particularly diverse in temperate regions, with the eastern Palaearctic and Nearctic regions containing the highest concentrations of taxa. The eight described African species are all restricted to temperateSouth Africa, most being found within the winter rainfall area of theWestern Cape (Hebauer, 1994). Here I describe a distinctive new species on the basis of specimens collected in the high Kamiesberg of Namaqualand in 2010. Specimens were studied using a Leica MZ8 stereomicroscope, with a Fluopac FP1 fluorescent illuminator. The habitus photograph was taken with a Canon EOS 600D camera fitted to a Leica Z6 Apo macroscope, fitted with a 2x objective lens. Specimens were illuminated using two Fluopac FP1 illuminators and a fibre-optic swan-neck illuminator to avoid shadow, light being diffused using a tracing-paper collar placed around the specimen. The aedeagus was traced from an image stack made using a Canon EOS 600D on a Brunel SP100 microscope at x 400 magnification. Image stacks were produced by hand, and combined using Helicon Focus software.